Genius Envy : Women Shaping French Poetic History, 1801-1900 - Paliyenko, Adrianna M., 1956- (Book collections on Project MUSE., 2016)
"Analyzes the reception of nineteenth-century French women poets, including Marceline Desbordes-Valmore, Amable Tastu, Élisa Mercoeur, Melanie Waldor, Louise Colet, Anaïs Segalas, Malvina Blanchecotte, Louise Ackermann, and Marie Krysinska, to recover the diversity of women's voices. Places their contributions within the medical and literary debate about the sex of genius"--Provided by publisher.